2015
DOI: 10.1002/ccd.25841
|View full text |Cite
|
Sign up to set email alerts
|

Successful versus unsuccessful antegrade recanalization of single chronic coronary occlusion: Eight‐year experience and outcomes by a propensity score ascertainment

Abstract: Successful PCI for single CTO does not improve long-term survival, nonetheless, is associated with reduced overall MACE and the need for surgical revascularization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Interestingly, in a post hoc analysis of the SYNTAX trial (n = 1800), nested PCI (n = 198), and nested CABG registries (n = 649), complete revascularization to patients with !1 CTO (PCI: 26.3%, CABG: 36.4%) was achieved more frequently in the CABG versus PCI group (68.1% versus 49.4%, p < 0.001); in the same report, incomplete revascularization was associated with higher 4year mortality in the whole cohort, as well as in the subgroup with CTO [57]. On the other hand, in patients with a single-vessel CTO, successful, versus failed, CTO-PCI was not associated with a longterm survival benefit [37,41]. Individually, survival benefit associated with successful, versus failed, CTO-PCI was consistent in the left anterior descending artery, but not in the left circumflex territory; lack of benefit was consistent in the right coronary artery [14,33].…”
Section: Reappraisal Of the Quality Of Evidencementioning
confidence: 85%
See 2 more Smart Citations
“…Interestingly, in a post hoc analysis of the SYNTAX trial (n = 1800), nested PCI (n = 198), and nested CABG registries (n = 649), complete revascularization to patients with !1 CTO (PCI: 26.3%, CABG: 36.4%) was achieved more frequently in the CABG versus PCI group (68.1% versus 49.4%, p < 0.001); in the same report, incomplete revascularization was associated with higher 4year mortality in the whole cohort, as well as in the subgroup with CTO [57]. On the other hand, in patients with a single-vessel CTO, successful, versus failed, CTO-PCI was not associated with a longterm survival benefit [37,41]. Individually, survival benefit associated with successful, versus failed, CTO-PCI was consistent in the left anterior descending artery, but not in the left circumflex territory; lack of benefit was consistent in the right coronary artery [14,33].…”
Section: Reappraisal Of the Quality Of Evidencementioning
confidence: 85%
“…On the other hand, studies that demonstrated comparable cardiovascular outcome with successful, versus failed, CTO-PCI are summarized in Table 4. All showed comparable mortality and other MACE between the two comparison groups, at long-term follow-up, either in adjusted, or in both adjusted and unadjusted analysis [3,18,20,[39][40][41][42][43]. However, as an inherent limitation to all registries and observational studies, the retrospective analysis of data could have introduced selection bias, added to the absence of information on the exact medical treatment received in the comparison groups.…”
Section: Impact On the Cardiovascular Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…Several observational studies have suggested that successful CTO PCI improves mortality rates [12,25] and MACE [12,25,26] when compared to failed CTO PCI, whereas one propensity score matched retrospective study revealed no difference in all-cause mortality [26]. Any possible improvement in outcome could be attributed to changes in cardiac function and positive remodeling [27,28].…”
Section: Clinical Outcomes Following Cto Pcimentioning
confidence: 99%
“…Polish data regarding usage of TRA in CTO are limited. Jaguszewski et al [5] in a series of 1110 CTO treated by antegrade approach from 2003 to 2010 reported no differences in success rate depending on the chosen access site. As described in the first Polish publication concerning recanalization of coronary chronic total occlusion by retrograde approach, in this special sub-set of procedures we used only femoral access [6].…”
Section: Introductionmentioning
confidence: 95%